Immobilization of lumbar spine instability in dogs - Kilic, S; Bulut, S (Indian Veterinary Journal, 2005)
The vertebral column instability may occur following fracture or luxation (Archhibald,1971). In the lumbar spine immobilization. Poly Methyl Methacrylate (PMMA) had been used either as subcutenous composite (Beaver et al., 1996; Harrington and Bageley, 1998) or as external fixation interconnecting bar (Garcia et al., 1994; Walker et al., 2002). The purpose of this study was to evaluate the efficacy of subcutaneous PMMA block for immobilization of experimentally. induced lumber spine instability.
Keywords: Vertebral Fracture-Luxations; Canine Model; Fixation; Repair; Polymethylmethacrylate; Fusion; Pins